Colour polymorphism in Salamandra salamandra (Amphibia: Urodela), revealed by a lack of genetic and environmental differentiation between distinct phenotypes. (25th January 2016) - Beukema, Wouter; Nicieza, Alfredo G.; Lourenço, André; Velo‐Antón, Guillermo
Abstract: The existence of two or more distinctly coloured phenotypes among individuals of an interbreeding population is known as colour polymorphism. In amphibians, this phenomenon is pervasive among anurans, but rare or absent among salamanders and caecilians, respectively. Here, we examine whether various distinct phenotypes of Salamandra salamandra in North Spain, used as a basis to describe the subspecies S. s. bernardezi and S. s. alfredschmidti, indeed warrant separate taxonomic status or that these co‐occur and belong to a single taxon. Based on a sample of 1147 individuals from 27 local populations, six phenotype classes were designated. Although two phenotypes that are attributable to S. s. alfredschmidti show some degree of geographical restriction, these co‐occur with those representing typical S. s. bernardezi . A fifth phenotype class could not be unambiguously attributed to either subspecies due to an overlap in previously suggested diagnostic characteristics. Mitochondrial (cytochrome b) and nuclear (β‐fibrinogen) DNA analyses revealed S. s. alfredschmidti to be nested within several subclades of S. s. bernardezi, without displaying unique lineages. Furthermore, no significant divergence was recovered by means of niche overlap analyses. As a result, we revoke the subspecies status of S. s. alfredschmidti, which should be regarded as a junior synonym of S. s. bernardezi . The current findings confirm the existence of colour polymorphism in S. salamandra and the family Salamandridae, which provides exciting possibilities for future research. Abstract : Based on phenotypic data, mitochondrial DNA analyses and niche modelling, we show that the North Spanish S. s. bernardezi and S. s. alfredschmidti belong to a single taxon, which is characterized by colour polymorphism. Mitochondrial data revealed that individuals hitherto attributed to S. s. alfredschmidti are imbedded in several subclades of S. s. bernardezi, with which they consistently occur syntopically. We confirm the existence of colour polymorphism in the family Salamandridae, which provides exciting possibilities for future research.